Optimizing the use of cadavers by integrating pathology during anatomy dissection. Issue 6 (3rd May 2016) - Geldenhuys, Elsje‐Márie; Burger, Elsie Helena; van Helden, Paul David; Mole, Calvin Gerald; Kotzé, Sanet Henriët
Abstract : An accurate knowledge of anatomy, especially natural variation within individuals, is of vital clinical importance. Cadaver dissection during anatomical training may be a valuable introduction to pathology for undergraduate students, which can contribute greatly to a successful medical career. The purpose of this study was to determine the extent and type of pathology lesions in a cadaver population ( n = 127) used for medical dissection. This was done to gauge whether sufficient pathology lesions representative of all the organ systems were present in the cadaver population to warrant the use of cadavers as an additional pathology learning resource. This study demonstrated a wide variety of pathology lesions in different organ systems. The respiratory system was most affected with pulmonary tuberculosis (TB) lesions being the most common finding (seen in 76% of cadavers) followed by bronchopneumonia and emphysema. Other common pathology findings included atherosclerosis, colonic diverticula, and chronic pyelonephritis. Skeletal fractures and degenerative joint disease were also noted. This study shows that cadaveric dissection offers a chance to alert and expose students to a wide variety of gross pathology and histopathology. It has been suggested that most medical students will practice in primary health care and as such more attention should be given to the pathology of commonly encountered diseases. This is particularly true for developing countries, where diseases such as TB are commonly encountered. The integration of pathology into the dissection hall may therefore be beneficial to student learning while simultaneously optimizing the use of cadaver material. Anat Sci Educ 9: 575–582. © 2016 American Association of Anatomists.